Papel da via óxido nítrico sintase neuronal/peróxido de hidrogênio (nNOS)/H2O2 em arteríolas mesentéricas humanas: implicações no controle da hipertensão arterial - Eduardo Damasceno Costa (2016)
H2O2 has been appointed as an endothelium-derived hyperpolarizing factor (EDHF) in different resistance vascular beds. The role of nNOS-derived H2O2 in vascular function and regulation of blood pressure in humans is so far unknown. The present study investigates the role of endothelium-dependent nNOS-derived H2O2 in the control of vascular function in human resistance mesenteric arteries and its involvement in the regulation of blood pressure in hypertensive patients. Vascular reactivity was evaluated in resistance mesenteric arteries from 67 subjects divided into three groups: normotensive patients (n=30), patients undertaking treatment with antihypertensives that had the blood pressure normalized (controlled hypertensive patients; n=19) and patients undertaking treatment with antihypertensives that remained hypertensive (uncontrolled hypertensive patients; n=18), on a wire myograph. Expression, functioning (Western blot) and localization (immunofluorescence) of eNOS, nNOS, vascular nitric oxide (NO; fluorescent DAF) and hydrogen peroxide (H2O2; fluorescent DCF) production, were also assessed. Vessels from uncontrolled hypertensive patients, showed an impaired endothelial-dependent vascular relaxation to ACh. However, vessels from controlled hypertensive patients showed similar relaxation to ACh compared to normotensive patients. L-NAME, a non-selective inhibitor of nitric oxide synthases (NOS), had a more pronounced inhibitor effect in the vascular relaxation from uncontrolled hypertensive patients compared to normotensive and controlled hypertensive patients. Conversely, inhibitor 1, a selective neuronal nitric oxide synthase (nNOS) inhibitor, had a lower effect in decreasing vascular relaxation in uncontrolled hypertensive patients compared to normotensive and controlled hypertensive patients. Catalase, that decomposes H2O2 into O2 and H2O, had major inhibitory effect in ACh-induced vascular relaxation in controlled hypertensive patients when compared to other two groups. Decreased eNOS expression was detected in both uncontrolled and controlled hypertensive patients. However, eNOS functioning was decreased only in uncontrolled hypertensive patients. Expression of nNOS was found to be increased only in controlled hypertensive patients. Functioning of nNOS was increased in controlled and uncontrolled hypertensive groups. Immunofluorescence analysis confirmed Western blot data. ACh-stimulated NO production was lower in controlled hypertensive when compared to normotensive patients, while uncontrolled hypertensive showed the smallest levels. Controlled hypertensive patients showed a higher ACh-stimulated H2O2 production compared to the two other groups of patients. It was also shown that the nNOS inhibitors (Inhibitor 1 and Trim) reduced ACh-induced production of H2O2 in controlled hypertensive patients but not in normotensive patients. nNOS-derived H2O2 contributes to the endothelium-dependent vascular relaxation in human resistance mesenteric arteries. The endothelial dysfunction observed in uncontrolled hypertensive patients is related to a decreased NO production secondary to reduction in eNOS functioning and expression.Regulation of blood pressure in hypertensive patients through the use of accurate medication involves a physiological compensatory mechanism related to an increased expression and functioning of nNOS in endothelial cells with consequent increase in H2O2 production.